Aplikasi Metode SDS-PAGE (Sodium Dodecyl Sulphate Poly Acrylamide Gel Electrophoresis) untuk Mengidentifikasi Sumber Asal Gelatin pada Kapsul Keras - Sandra Hermanto; Fahrur Rahman Saputra; Zilhadia . (Jurnal Kimia Valensi, 2015)
Gelatin as the main ingredient of capsules is still a problem for a moslem. Most of gelatin production remains largely derived from non-halal materials. One of gelatin source is came from collagen of the skin and bones of bovine or pork. The main of study is determine the source of gelatin used in hard capsules by using SDS-PAGE (Sodium Dodecyl Sulphate Gel electrophoresis Poly Acrylamide) method. In the early stages, optimization of standards bovine and pork gelatin were hydrolyzed by pepsin at pH 4.5 and 60°C for 1 hour, 2 hours, and 3 hours. Gelatin hydrolyzateswere analyzed by SDS-PAGE to determine the optimal hydrolysis time. Identification of gelatin hydrolyzate fragments were carried by molecular weight. Hydrolysis time optimization throught applied to identify the source of hard gelatin capsules in the samples obtained from market and compared with the simulation of hard gelatin capsules. The results showed there were of specific bands of bovine gelatin with a molecular weight of 11,4 kDa; 34 kDa; 47kDa and specific bands of pork gelatin with a molecular weight of 24.7 kDa; 28 kDa; and 60 kDa. Similar results were obtained on a sample of hard capsules with bands of protein fragments that were identical to bovine gelatinstandard. Based on the results,each of the samples were tested contain of bovine gelatin respectively. DOI :http://dx.doi.org/10.15408/jkv.v0i0.3150